VD_FINDINFO Arrêt / 2023 / 658 vom 25. September 2023 - VD Tribunal cantonal (2023)
LOI FÉDÉRALE SUR L'ASSURANCE-ACCIDENTS, COTISATION DE L'EMPLOYEUR | 1a al. 1 LAA, 92 LAA, 5 al. 2 LAVS, 52 al. 3 LPGA, 53 LPGA, 1 OLAA, 22 al. 2 OLAA